Medfly Gut Microbiota and Enhancement of the Sterile Insect Technique: Similarities and Differences of Klebsiella oxytoca and Enterobacter sp. AA26 Probiotics during the Larval and Adult Stages of the VIENNA 8D53+ Genetic Sexing Strain - Kyritsis, Georgios A.; Augustinos, Antonios A.; Cáceres, Carlos; Bourtzis, Kostas (Frontiers in Microbiology, 2017)
The Mediterranean fruit fly, Ceratitis capitata, is a major agricultural pest worldwide. The development of genetic sexing strains for this species that allows male-only sterile insects releases has boosted the effectiveness of the environmental friendly pest control method known as the sterile insect technique. The last generation of these strains, the VIENNA 7 and VIENNA 8, are currently used in all mass rearing facilities worldwide and are considered as models for such pest control applications. The sterile insect technique depends on the rearing of sufficient numbers of adequate “biological quality” laboratory flies to be released in the field. Currently, there is an increasing amount of studies focusing on the characterization of the symbiotic communities and development of probiotic diets. In our study, two bacterial isolates, an Enterobacter sp. (strain AA26) and a Klebsiella oxytoca strain, were used as probiotics in larval and adult diet. These strains have been shown to be beneficial, affecting several aspects related to the rearing efficiency and biological quality of the medfly VIENNA 8D53+ genetic sexing strain. Our results demonstrate the effect of Klebsiella oxytoca on the developmental duration of the immature stages and, to some extent, on flight ability. On the other hand, our study does not support the presence of any beneficial effect of a) Klebsiella oxytoca on pupal and adult recovery and adults’ survival under stress conditions when provided as a larval diet supplement and b) Klebsiella oxytoca and Enterobacter sp. AA26 on mating competitiveness when provided as adult diet supplements. Possible explanations for inconsistencies with previous studies and the need for universalizing protocols are discussed. Our findings, combined with previous studies can support the sterile insect technique, through the improvement of different aspects of mass rearing and biological properties of laboratory reared insect pests.